An Evaluation of the “Kohikohi Kitea Kohikohi Kōrero: Hayman Park Engagement with Children and Whānau” Project - Chumpunuch, Pornchanuch (Auckland University of Technology, 2017)
This research aims to explore how well the “Kohikohi Kitea Kohikohi Kōrero: Hayman Park Engagement with Children and Whānau” project, a consultation with community members about designing a park playground, meets the needs of community members. Here, I seek to identify what local people can gain from participating in a consultation project. I use a qualitative research approach to elucidate participants’ perceptions post project. I assess two children’s focus group transcripts and conduct three face-to-face interviews with adult participants. I identify three main categories: health and well-being; community and individual needs; and the effectiveness of community partnership. I find that the Hayman Park project enables research participants to gain health and well-being benefits. They also gain knowledge about community partnership. Therefore, I conclude that this project meets the needs of the local community. However, the project does not fulfil participants’ desires for more meaningful engagement with other stakeholders in the playground design process.
Keywords: Designing playground; Community partnership; Raising awareness; Children as effective partners; Balance of knowledge; Sense of being valued; Sense of belonging; Community-based participatory research; Knowing the real need